2022
DOI: 10.1002/ijc.34313
|View full text |Cite
|
Sign up to set email alerts
|

Sex and smoking differences in the association between gastroesophageal reflux and risk of esophageal squamous cell carcinoma in a high‐incidence area: Golestan Cohort Study

Abstract: Prior studies have conflicting findings regarding the association between gastroesophageal reflux disease (GERD) and esophageal squamous cell carcinoma (ESCC). We examined this relationship in a prospective cohort in a region of high ESCC incidence. Baseline exposure data were collected from 50 045 individuals using in‐person interviews at the time of cohort entry. Participants were followed until they developed cancer, died, or were lost to follow up. Participants with GERD symptoms were categorized into any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…Although GERD was not previously recognized as a risk factor for ESCC [48], a prospective cohort study of almost 500,000 participants in the United States showed a two-fold increased ESCC risk among individuals with GERD during a 16-year follow-up period [122]. However, another prospective cohort study of 50,000 participants in a highrisk region of Iran showed no increase in ESCC risk among individuals with GERD during a 13-year follow-up period [123].…”
Section: Gastroesophageal Reflux Disease (Gerd)mentioning
confidence: 97%
“…Although GERD was not previously recognized as a risk factor for ESCC [48], a prospective cohort study of almost 500,000 participants in the United States showed a two-fold increased ESCC risk among individuals with GERD during a 16-year follow-up period [122]. However, another prospective cohort study of 50,000 participants in a highrisk region of Iran showed no increase in ESCC risk among individuals with GERD during a 13-year follow-up period [123].…”
Section: Gastroesophageal Reflux Disease (Gerd)mentioning
confidence: 97%
“…There was a significant male predominance in EC cases with a male-to-female incidence ratio of 3.3:1 for ESCC and 6.7:1 for EAC [ 8 ]. Further, the interaction effect of sex and smoking in ESCC has been reported in a cohort study with 13 years of median follow-up [ 12 ]. However, comprehensive understanding of EC risk–attributable burden does not exist in many countries, leading to a void in the up-to-date prevention strategies and adjustment in the EC treatment research focus.…”
Section: Introductionmentioning
confidence: 99%